2019
DOI: 10.1177/1747954119848420
|View full text |Cite
|
Sign up to set email alerts
|

Psychological contract, job satisfaction, commitment, and turnover intention: Exploring the moderating role of psychological contract breach in National Collegiate Athletic Association coaches

Abstract: This study examined the relationship between psychological contract and three work attitudes, job satisfaction, affective commitment, and turnover intention in a sample of National Collegiate Athletic Association coaches. This study also explored the moderating role of the psychological contract by examining coaches' perceptions of the intentional and unintentional breach. A total of 383 coaches responded to the survey that included items in the transactional and relational psychological contract, job satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…This study found an indirect effect (H6), turnover intention is a partially mediated relationship between psychological contract breach and employee well-being. This finding is consistent with prior studies (Vaart et al, 2013;Bravo et al, 2019). They suggested that employers must devise employee-friendly policies to enhance workplace wellbeing as a retention strategy.…”
Section: Discussionsupporting
confidence: 91%
“…This study found an indirect effect (H6), turnover intention is a partially mediated relationship between psychological contract breach and employee well-being. This finding is consistent with prior studies (Vaart et al, 2013;Bravo et al, 2019). They suggested that employers must devise employee-friendly policies to enhance workplace wellbeing as a retention strategy.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, they will be more likely to reduce their obligations as a form of revenge ( Christian and Ellis, 2014 ). Turnover intention is strongly predicted by psychological contract breaches in the relationship between individuals and an organization ( Bravo et al, 2019 ). Prior research has indicated that turnover intention dampens employees’ relational contracts ( Burris et al, 2008 ; Bravo et al, 2019 ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Turnover intention is strongly predicted by psychological contract breaches in the relationship between individuals and an organization ( Bravo et al, 2019 ). Prior research has indicated that turnover intention dampens employees’ relational contracts ( Burris et al, 2008 ; Bravo et al, 2019 ). Once an employee decides to leave, their relational contract perception has changed; they are consciously disrupting the bonds of the contracts and do not consider what they owe their employer.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…A violation of the expectations of the implied or non-explicit agreements would be considered a breach. This violation is considered a good ground for turnover (Bravo, Won & Chiu, 2019). Workers and their employers have expectations of reciprocity, which is the belief that the organisation will provide rewards that match the effort of the workers, though one of the challenges is covering workers' expectations of reciprocity and recognising unmet expectations (Kanu, Ugwu, Ogba, Ujoatuonu, Ezeh, Eze, Okoro, Agudiegwu, & Ugwu, 2022).).…”
Section: Expectationsmentioning
confidence: 99%